Potentialy Of Flavonoid Miana (Coleus Atropurpereus) Leaves Estract As Anti Mycobacterium Tuberculosis H37rv Strain And Mdr With Microscopy Observation Drug Susceptibility (Mods) - Anita Anita; Dewi Arisanti; Andi Fatmawati (Universitas Hasanuddin, 2018)
There is high resistance cases for Isoniazid and Rifampin and more famous withMulti-drug resistant tuberculosis (MDR-TB). From data in Makassar, South sulawesishowed 19,2 MDR-TB cases from new TB patient, and more 13,5% resistance cases forfirstline-TB drugs (STR, INH, RIF,and ETH), and >2 resistance for secondline-TBdrugs (OFL,KAN,AMK). Treatment for tuberculosis mostlly not effective because Multidrugresistanttuberculosis (MDR-TB) cases is very high.WHO recomended traditionalmedicine for improvement of healthy in coummunity, preventive and pharmaceuticalpreparation for all diseases. Research in 2013 showed 85,71% that Torajas TB patientin South Sulawesi used traditional medicine such as Miana (Coleus atropurpereus)leaves estract as complement for TB drugs. Our study showed flavonoid component fromqualitative method used sianida (HCl-Mg) from ethanol 96% Miana (Coleusatropurpereus) leaves estract .Qualitative method using Spektrofotometer UV-V showedthe total of flavonoid component from ethanol 96% miana (Coleus atropurpereus) leavesestract is 8,59 mgRE/gram ekstract.. The result showed were at concentrations (10%,20% ,40 % , 60 % ,80 % and 100%) ethanol 96% miana (Coleus atropurpereus) leavesestract were effecttively inhibit Mycobacterium tuberculosis H37RV strain. Were atconcentration (10%, 20% ,40 % dan 60 %) ethanol 96% miana (Coleus atropurpereus)leaves estract were not effecttively inhibit MDR-TB but effecttively were at concentration (80 % and 100%).